Hubungan Paritas, Biaya dan Pendidikan dengan KB Implant - Nuraini Nuraini; Siti Aisyah; Putu Lusita Nati Indriani (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Family planning (KB) is an act that shapes an individual or a married couple to get certain objectives. Objective: To determine the relationship between parity, cost and education with implant family planning. This type of research is quantitative using an analytic survey with a cross sectional study approach to see the momentary relationship between the independent and dependent variables. The samples in this study were all women of childbearing age who were active family planning participants. The time of data collection in this study was carried out on February 12, 2020, and the data collection process was carried out on June 25 to August 18, 2020, statistical tests using the Chi-Square Test. The results of the research of respondents who did not use implant family planning (57.9%), respondents whose parity was at risk as much as (32.6%), respondents who had the cost of implanting FP implants independently were (60.0%) and those who were Implant using BPJS as much (40.0%). Meanwhile, respondents with low education were (40%). The statistical test results show that there is no significant relationship between parity (p-value = 0.363), there is a relationship between costs (p-value = 0.003), and education (p-value = 0.000). It is hoped that the health team in community services will be more active in providing training for obstetricians who are related to family planning implant acceptors.